Canine Primary Intracranial Cancer: A Clinicopathologic and Comparative Review of Glioma, Meningioma, and Choroid Plexus Tumors - Miller, Andrew D.; Miller, C. Ryan; Rossmeisl, John H. (Frontiers in Oncology, 2019)
In the dog, primary intracranial neoplasia represents 2–5% of all cancers and is especially common in certain breeds including English and French bulldogs and Boxers. The most common types of primary intracranial cancer in the dog are meningioma, glioma, and choroid plexus tumors, generally occurring in middle aged to older dogs. Much work has recently been done to understand the characteristic imaging and clinicopathologic features of these tumors. The gross and histologic landscape of these tumors in the dog compare favorably to their human counterparts with many similarities noted in histologic patterns, subtype, and grades. Data informing the underlying molecular abnormalities in the canine tumors have only begun to be unraveled, but reveal similar pathways are mutated between canine and human primary intracranial neoplasia. This review will provide an overview of the clinicopathologic features of the three most common forms of primary intracranial cancer in the dog, delve into the comparative aspects between the dog and human neoplasms, and provide an introduction to current standard of care while also highlighting novel, experimental treatments that may help bridge the gap between canine and human cancer therapies.